PENGARUH POTONGAN HARGA (DISCOUNT) TERHADAP PEMBELIAN TIDAK TERENCANA (IMPULSE BUYING) (STUDI PADA PENGUNJUNG MATAHARI DEPARTMENT STORE JOHAR PLAZA JEMBER) - Baskara, Indra Bayu (Manajemen Bisnis, 2015)
The purpose of this research was to analyze the response of impulse buying, response to discount on Matahari Department store and  the effect of  discount on impulse buying on visitors. The population in were the visitors at Matahari Department Store, the number of samples 100 visitors who were collected by using purposive sampling technique. The analysis technique was descriptive analysis and the simple linear regression. The result of descriptive analysis shows that the response of impulse buying was positive and the response of discount was also positive. The result of simple linear regression show that impulse buying was influenced by discounted price (discount) on Matahari Department Store. The positive results  tend to be weak indicated by the results of adjusted R-square. This mean that  the impulse buying in Matahari Department Store was also  influenced by other variables outside of this research